STRATEGI KEPARIWISATAAN PADA DINAS KEBUDAYAAN DAN PARIWISATA KOTA PEKANBARU - ROBBY DESMAN INDRA SAPUTRA; TUTI KHAIRANI HARAHAP (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The strategy of tourism at culture and tourism service of pekanbaru. The objective ofthis research was to find out the implementation of tourism’s strategy at culture and tourismservice of pekanbaru. This research is a qualitative research and the writer using snowballtechnique to collect the data. Based on the result of the research, the writer had concluded thatthe implementation of tourism’s strategy by the culture and tourism service of pekanbaru was notrunning well, its evidenced by the lack of infrastructures as a tourism promotion, lack of budgetas construction and tourism’s development, and the employee’s quality who has not executed thestrategy that has been formulated in a maximum portion.Keywords : strategy, implementation,tourism